Educators working together for interprofessional education: From "fragmented beginnings" to being "intentionally interprofessional". Issue 5 (2nd September 2016) - Croker, Anne; Wakely, Luke; Leys, Jacqueline
ABSTRACT: This article explores the development of interprofessional relationships between healthcare educators working together for interprofessional education (IPE). As part of a collaborative dialogical inquiry, data from 19 semi-structured interviews and 9 focus groups were used to explore how IPE educators develop shared purpose to help students learn to work with other health professions. Consistent with this methodology, the research group and study participants comprised educators from eight different professions. Questions asked of the data, using a lens of intersubjectivity, included: "What implicit assumptions are brought to interactions?" and "What happens to these assumptions as educators interact?" The emergent themes caution against assuming that all educators initially bring to interprofessional spaces only positive attitudes towards all professions. Educators beginning in a fragmented interprofessional space needed to reflect on earlier negative experiences with particular professions for reframing in a socially aware interprofessional space to enable collaborating in an intentional interprofessional space .